SURGICAL METHODS FOR THE CORRECTION OF RENAL FUNCTION DISORDERS IN CHILDREN (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Research objective. To study the results of the development of surgical approaches, improvement of materials for endoscopic correction, and refinement of robotic technologies, which open up prospects for improving the effectiveness of VUR treatment. Materials and methods. From 2018 to 2025, 120 children with vesicoureteral reflux were examined and treated at the TashPMI clinic. All patients were selected for treatment based on the degree of VUR. Results. This article reviews modern methods of surgical treatment of VUR, their indications, advantages, and disadvantages. Modern surgical technologies, including robot-assisted and laparoscopic techniques, reduce the invasiveness of the procedure, shorten the recovery period, and minimise the risk of complications.